158. The Effect of Insurance Coverage on Appropriate Selection of Hospital Discharge Antibiotics for Staphylococcus aureus Bacteremia. (26th November 2018) - McHale, Thomas; Medder, Jim; Lyden, Elizabeth; Geske, Jenenne; Rupp, Mark E; Van Schooneveld, Trevor
Abstract: Background: Inappropriate or inadequate antimicrobial therapy of Staphylococcus aureus bacteremia (SAB) is associated with worsened outcomes. The impact of insurance coverage on appropriate selection of antibiotics is poorly understood. In patients diagnosed with SAB, we assessed the impact of insurance coverage on appropriate selection and duration of antibiotics at discharge. Methods: We analyzed 273 patients who were diagnosed with SAB during their hospitalization at Nebraska Medicine and were discharged on antibiotics in 2015 and 2016. Antimicrobial therapy was deemed inappropriate if (i) total treatment duration was less than 14 days, (ii) oral delivery route was used, (iii) vancomycin was used to treat methicillin sensitive S. aureus in non-β-lactam allergic patients, or (iv) any penicillin or cephalosporin was used to treat methicillin-resistant S. aureus . Insurance was categorized broadly into (i) no insurance, (ii) Medicaid, (iii) Medicare, and (iv) Commercial. We collected data on a suite of additional variables that included: type of infectious disease (ID) inpatient consult and location of discharge. Logistic regression was used to determine the odds of being prescribed inappropriate therapy in univariate and multivariate analyses and likelihood ratio tests (LRT) were used to evaluate the strength of evidence. Results: In unadjusted models, not having insurance was associated with inappropriate antimicrobial therapy (Reference Group: Any insurance; OR No insurance 4.71; LRT P = 0.027). Two additional risk factors for inappropriate therapy were identified in unadjusted models: discharge location (Refrence Group: Nursing assistance; OR Home without assistance 3.37; 95% CI 1.34–8.46; LRT P = 0.008) and lack of an ID consult (Reference Group: Academic team; OR Not consulted 26.8, 95% CI 7.66–93.8; LRT P < 0.001). Conclusion: We found strong evidence that not having insurance, being discharged to home without assistance, and not having an inpatient ID consult are risk factors for being prescribed inappropriate antimicrobial therapy for SAB upon hospital discharge; however, the sparsity of outcomes prevents us from drawing causal inferences. This study adds to the extensive body of evidence that has shown that uninsured patients tend to have suboptimal therapeutic choices. Disclosures: All authors: No reported disclosures.